Human Resource for Health in Nepal - A, Magar (Journal of Nepal Health Research Council, 2013)
Human Resources for Health is defined as â€œall peopleengaged in actions whose primary intent is to enhancehealthâ€, according to the World Health Organization's(WHO).1 The HRH is one of the building block of healthsystem which includes doctors, nurse, dentists, alliedhealth professions, community health workers, socialhealth workers and other health care providers, as wellas health management and support personnel â€“ thosewho may not deliver services directly but are essentialto effective health system functioning, includinghealth services managers, medical records and healthinformation technicians, health economists, healthsupply chain managers, medical secretaries, and others.